Qalat-e-Shah: a Median or Islamic Watch Tower in Northwestern Iran? - Binandeh, Ali; Hossein Rezaei, Mohammad; Sorkhabi, Obeidollah (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2023)
The Shah’s Watchtower is a fortress situated in a remote and inaccessible region in the northwest of Iran, near Lake Urmia. The fortress, now in ruins, consists of two separate building structures, with only the foundations remaining. These structures are rectangular and square in shape, featuring multiple interconnected rooms and corridors. Surrounding the fortress are irregular pools designed for rainwater collection. Additionally, underneath the main rock, there is a cave-like stony sanctuary with a spring. An archaeological investigation conducted in 1975 compared the architectural features of the Shah’s Watchtower to other Urartian castles in the vicinity. Based on this comparison, it was initially suggested that the fortress was constructed during the first millennium BC. However, recent surveys and studies have challenged this proposed chronology. The architectural style and structure of the Shah’s Watchtower deviate from those of other forts from the same period in northwestern Iran. Furthermore, the pottery fragments discovered at the site do not align with the typical pottery of the first millennium BC. This discrepancy raises the possibility that the site may be associated with the late Islamic centuries. Further research is needed to establish a more precise chronology and to better understand the cultural and historical significance of the Shah’s Watchtower.